Tracing Islamic Educational Values in Qur'anic Revelation and Compilation: A Historical Study - Ratnasari, Dwi (Jurnal Pendidikan Islam, 2022)
Purpose – The purpose of this research is to explore the historical development of Islamic education values within the context of the Qur'anic revelation and its compilation. The study also aims to examine the significance of the Qur'an in shaping Islamic educational values and to trace the evolution of these values over time. Design/methodology/approach – The historical research method was employed in this study to investigate the development of Islamic education values within the context of the Qur'anic revelation and compilation. Data collection involved various sources, including written materials such as Qur'anic manuscripts, history books, and literature on Islamic education, as well as oral sources such as interviews with experts on history and Islamic education. Findings – The research findings suggest that the Qur'an has been the primary source of Islamic educational values and has had a significant impact on the development of Islamic education. The Qur'an has influenced the fundamental principles and values of Islamic education, including the pursuit of knowledge, moral values, and social justice. The study also shows that the evolution of Islamic education values has been influenced by historical events and changes in Islamic societies, but the basic principles have remained consistent over time. Research implications/limitations – The limitations of the research are that it does not examine the long-term effects of internalizing Islamic moderation values on children's overall development and well-being and does not provide insights into the potential consequences or benefits of this process. Future research may need to investigate the long-term impact of these values to provide a more comprehensive understanding of their significance for the development of Muslim communities. Practical implications – This research provides insights into the potential ways of integrating Islamic education values into modern educational settings and contributes to the development of more inclusive and culturally sensitive educational practices.